An Objective Comparison of Vedolizumab and Ustekinumab Effectiveness in Crohn's Disease Patients' Failure to TNF-Alpha Inhibitors. (13th August 2022) - Onali, Sara; Pugliese, Daniela; Caprioli, Flavio Andrea; Orlando, Ambrogio; Biancone, Livia; Nardone, Olga Maria; Imperatore, Nicola; Fiorino, Gionata; Cappello, Maria; Viola, Anna; Principi, Maria Beatrice; Bezzio, Cristina; et al.
Abstract : INTRODUCTION: The use of ustekinumab and vedolizumab as second-line therapies in patients with Crohn's disease (CD) in which tumour necrosis factor alpha inhibitors (TNFi) failed is still debated. The aim of this study was to compare, in a large multicenter observational retrospective cohort, the effectiveness of ustekinumab and vedolizumab as second-line therapies, as assessed by clinical and objective outcomes including endoscopy and gastrointestinal imaging. METHODS: Clinical response, remission, and steroid-free remission at weeks 26 and 52 were evaluated in a retrospective propensity score–weighted and propensity score–matched cohort of patients in which TNFi failed. Objective response and remission were evaluated by 1 or more techniques among endoscopy, magnetic resonance/computed tomography enteroclysis, and small bowel ultrasound. RESULTS: A total of 470 patients with CD (239 treated with ustekinumab and 231 treated with vedolizumab) were included in the study. At week 26, clinical outcomes were similar between the 2 groups. At week 52, clinical remission (ustekinumab 42.5% vs vedolizumab 55.5%, P = 0.01) and steroid-free remission (ustekinumab 40.6% vs vedolizumab 51.1%, P = 0.038) rates were significantly higher in vedolizumab-treated patients. Three hundred two patients (hundred thirty-five treated with ustekinumab and hundred sixty-seven treated with vedolizumab) had an objective evaluation of disease activity at baseline and week 52. At week 52, objective response and remission rates were similar between the 2 groups. Clinical response at week 26 predicted steroid-free remission at week 52 in both ustekinumab-treated and vedolizumab-treated patients. Safety profiles were similar between the 2 groups. DISCUSSION: In patients with CD in which TNFi failed, both ustekinumab and vedolizumab showed similar clinical effectiveness after 26 weeks of treatment. At 1 year, vedolizumab was associated with a higher rate of clinical remission when compared with ustekinumab. However, no difference was observed between the 2 groups when objective outcomes were investigated at this time point. Abstract :